Design and Development of a Maturity Model for Performance Evaluation of Managers with a Modern Technology Approach in Bank Melli Iran (Fuzzy Delphi Method) - Kyiani Ghalenoo, Ehsan; Salarzehi, Habibollah; Naseri, Bahareh; Keshtegar, Abdolali (International Journal of Innovation Management and Organizational Behavior (IJIMOB), 2024)
Objective: Industry 4.0 or the digital revolution is changing the way we live, altering the interaction between customers and banks, inevitably implying that both existing business techniques and financial management are not exempt from this change. The main objective of this research is to design and develop a maturity model for the performance evaluation of managers in Bank Melli Iran with a modern technology approach.Methodology: This research is applied-developmental in terms of purpose, exploratory in nature, and descriptive-survey with a mixed exploratory approach in terms of data collection method. The qualitative approach is based on the fuzzy Delphi method. In the qualitative section of the research, a purposeful sample of 15 participants was selected, including academic experts and some senior managers of Bank Melli.Findings: The statistical population in the quantitative section includes 180 experts and employees of Bank Melli, with a sample size of 120 estimated using random sampling. Data in the qualitative section were collected through semi-structured interviews guided by general directions and then analyzed using the fuzzy Delphi method to develop the conceptual model of the research. In the model testing phase, the research hypotheses were developed and tested using factor analysis and path analysis models with SPSS and PLS software.Conclusion: The research results indicated that the model consists of four main factors: management tasks, conceptual skills, technical skills, and human skills, described by 22 indicators and 104 sub-indicators.